Benefits of internal manufacturing network integration: The moderating effect of country context. Issue 7 (4th July 2016) - Szász, Levente; Scherrer-Rathje, Maike; Deflorin, Patricia
Abstract : Purpose: – The purpose of this paper is to offer deeper insight into the relationship between a subsidiary's internal integration in its manufacturing network and subsidiary-level operational performance by taking into account the country context of the respective subsidiary. Design/methodology/approach: – Subsidiary-level information is gathered using the sixth round of the International Manufacturing Strategy Survey, thus including 507 subsidiaries from 22 countries. Country context is operationalised using the Global Competitiveness Report published by the World Economic Forum. Findings: – The findings reveal that internal integration has a positive influence on operational performance improvement. Country context acts as a moderator on this relationship: subsidiaries in less developed countries are only able to improve their effectiveness (quality, flexibility, delivery), while developed country subsidiaries gain both effectiveness and efficiency (cost, time) benefits from internal integration. Research limitations/implications: – The unit of analysis is the knowledge-receiving subsidiary without taking the characteristics of the sending unit or that of the whole network of subsidiaries into account. Based on the context-dependency of the integration-performance relationship found in this paper, a future research agenda is proposed including further factors (absorptive capacity, knowledge complementarity, organisational practices) that could influence this relationship. Practical implications: – Subsidiary managers in less developed countries should strive to acquire intra-network knowledge related to effectiveness, while managers in developed countries can expect both efficiency and effectiveness benefits. Originality/value: – A large-scale survey encompassing subsidiaries from both emerging and developed countries is used to offer deeper insight into the relationship between internal integration and performance. The paper provides a possible explanation for previous mixed findings on this relationship. The differentiation between efficiency and effectiveness performance shows that country context represents an important factor that moderates the integration-performance relationship.